AB0932 Frequency of Vertebral Fracture on Lateral Vertebral Assessment in Patients with Osteopenia Undergoing DXA Scanning. (15th July 2016) - Alshamsi, A.; Barry, M.; Murphy, E.; Corry, C.; Duffy, T.
Abstract : Background: Previous low trauma fracture is a strong predictor of future fracture. Lateral Vertebral Assessment (LVA) is useful to screen for preexisting but undiagnosed vertebral fracture. It is however commonly not performed at the time of DXA scanning. Anti resorptive therapy is frequently withheld in patients with Osteopenia on DXA as fracture risk is perceived not to be high. This perception might change if LVA performed at the time of DXA scanning demonstrated previous fracture. Objectives: The aim of this study was to measure the frequency of vertebral fracture on LVA in patients found to have Osteopenia on DXA. Methods: DXA scans from 170 female patients from two centers in Ireland (Connolly Hospital/Clane Hospital) performed in 2013/2014 were analyzed retrospectively. Patients ranged in age from 40 to 90 years. All patients had T-score between -1.0 and -2.5. They underwent Lateral Vertebral Assessment at the same session following BMD measurement. All patients are scanned by the same certified densitometry technologist at both centers, using quantitive (vertebral morphometry) and semiquantitative (visual assessment). The scans were reported by a consultant Rheumatologist and Rheumatology registrar. A vertebral fracture was diagnosed if identified by all 3 reviewers. Results: 41 out of 170 Osteopenic patients i.e 24% had vertebral fractures seen on LVA. 51 fractures in total were identified, involving 32 thoracic and 19 lumbar vertebrae. They all occurred in those above 50 years of age, and the frequency of fractures increased with age. 43 of the fractures were classified as mild, 3 as moderate and 5 as severe fractures according to Genant et al. [4]. Conclusions: Our study emphasizes the importance of LVA in identifying vertebral fractures in osteopenic patients. In view of its advantages, we suggest that any patient undergoing DXA assessment should have an LVA performed regardless of age. References: Burger H, Van Daele PLA, Gashuis K et al (1997) Vertebral deformities and functional impairment in men and women. J Bone Miner Res 12:152–157 Fink HA, Ensrud KE, Nelson DB et al (2003) Disability after clinical fracture in postmenopausal women with low bone density: The Fracture Intervention Trial (FIT). Osteoporos Int 14:69–76 P. L. Jager, S. Jonkman, W. Koolhaas, A. Stiekema, B. H. R. Wolffenbuttel. And R. H. J. A. Slart. (2011). Combined vertebral fracture assessment and bone mineral density measurement: a new standard in the diagnosis of osteoporosis in academic populations. Osteoporos Int Apr; 22 (4): 1059–1068. G. Guglielmi, D. Diacinti, C. Van Kuijk, F. Aparisi, C. Krestan, J. E. Adams, T. M. Link. Vertebral morphometry: current methods and recent advances. Eur Radiol (2008) 18: 1484–1496 DOI 10. 1007/s00330–008–0899–8 Acknowledgement: Rheumatology team in Connolly Hospital: Dr Maurice Barry, Dr Ethine Murphy, Dr Trevor Murphy, Dr John Stalk (SPR). Rheumatology Secretaries. Catherine Corry: Technologist in Dexa Scan from Clane Hospital. Disclosure of Interest: None declared